Unmasking The Hidden Clues: Shedding Light On The Potential Of Novel Biomarkers In Endometrial Cancer, Comparing RT-Qpcr And Immunohistochemical Analysis In Clinical Specimens - Sampana Fatima; Ayman Sabora; Iqra Anwar; Seher Naeem; Muhammad Abrar (Journal of Rawalpindi Medical College)
Objective: The objective of this study was to compare the diagnostic accuracy of RT-qPCR in endometrial cancer using novel biomarkers in clinical specimens, keeping immunohistochemical analysis as the gold standard.